2013
DOI: 10.1038/cddis.2013.126
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 contributes to CNS axon regeneration upon inflammatory stimulation

Abstract: Mature retinal ganglion cells (RGCs) do not normally regenerate injured axons and undergo apoptosis after axotomy. Inflammatory stimulation (IS) in the eye mediates neuroprotection and induces axon regeneration into the injured optic nerve. Ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF) have been identified as key mediators of these effects. Here, we investigated the role of interleukin-6 (IL-6), another member of the glycoprotein 130-activating cytokine family, as additonal contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 59 publications
5
112
0
Order By: Relevance
“…2,5,[17][18][19]36,37 However, these effects appear rather moderate in comparison to genetic depletion of SOCS3 or PTEN, which act as cell-intrinsic inhibitors of cytokine-induced signaling pathways. 6,[21][22][23] Consequently, naive IL-6-type cytokines, released after IS or applied at high and sustained levels, are seemingly insufficient to induce optimal gp130 signaling in injured neurons.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,[17][18][19]36,37 However, these effects appear rather moderate in comparison to genetic depletion of SOCS3 or PTEN, which act as cell-intrinsic inhibitors of cytokine-induced signaling pathways. 6,[21][22][23] Consequently, naive IL-6-type cytokines, released after IS or applied at high and sustained levels, are seemingly insufficient to induce optimal gp130 signaling in injured neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the mice in these experiments were from a Bax WT background to enable direct comparison with the original PTEN deletion data (Park et al, 2008); however, this means that possible survivalpromoting effects of the mutant alleles cannot be excluded. The extent of regeneration achieved by direct genetic activation of specific intracellular signaling pathways, including B-RAF, DLK, PI3-kinase-mTOR, KLF, and JAK-STAT pathways Yan et al, 2009;Park et al, 2010;Blackmore et al, 2012;Shin et al, 2012;Lang et al, 2013), compares favorably with what has been reported for application of growth factors such as NGF, BDNF, GDNF, and CNTF (Lykissas et al, 2007;Zhang et al, 2009;Allen et al, 2013;Leibinger et al, 2013). Growth factors as promoters of regeneration are hobbled by two major issues.…”
Section: Kab-raf Expression and Pten Deletion Synergize To Increase Amentioning
confidence: 99%
“…41 The complex binding of IL-6 to the receptor requires further association with glycoprotein 130 (gp130) before generating a downstream signal transduction. 42 Recently, Leibinger et al 43 found that optic nerve injury triggered upregulation of IL-6 and the binding of IL-6 to its receptor on the retina, via activation of JAK/STAT3 transduction pathway, ultimately promoted neurite outgrowth and prolonged survivability of mature retinal ganglion cells in Table 2. Clinical application of EPO for treatment of ocular disorders SL Shirley Ding et al culture.…”
Section: The Role Of Epo In the Eyementioning
confidence: 99%